Factors Associated with Late Local Radiation Toxicity after Post-Operative Breast Irradiation. (16th April 2022) - Batenburg, M.C.T.; Bartels, M.; Maarse, W.; Witkamp, A.; Verkooijen, H.M.; van den Bongard, H.J.G.D.
Abstract : Purpose . To assess determinants associated with late local radiation toxicity in patients treated for breast cancer. Methods . A systematic review was performed. All studies reporting ≥2 variables associated with late local radiation toxicity after treatment with postoperative whole breast irradiation were included. Cohort studies, randomized controlled trials, and cross-sectional studies were eligible designs. Study characteristics and definitions of determinants and outcome measures were extracted. If possible, the measure of association was extracted. Results . Twenty-one studies were included in this review. Six out of seven studies focused on the association between radiotherapy (boost) dose or irradiated breast volume and late radiation toxicity found significant results. Tumor bed boost was associated with late radiation toxicity, fibrosis, and/or edema in six out of twelve studies. Lower age was associated with late breast toxicity in one study, while in another study, higher age was significantly associated with breast fibrosis. Also, no association between age and late radiation toxicity was found in eight out of twelve studies. Similar inconsistent results were found in the association between late radiation toxicity and other patient-related factors (i.e., breast size, diabetes mellitus) and surgical and systemic treatment-related factors (i.e., complications after surgery, chemotherapy, and time between surgery and radiotherapy). Conclusion . In modern 3D radiotherapy, radiotherapy (boost) dose and volume are—like in 2D radiotherapy—associated with late local radiation toxicity, such as breast fibrosis and edema. Treatment de-escalation, for example, partial breast irradiation in selected patients might be important to decrease late local toxicity without compromising locoregional control and survival.